Variable selection patterns on the labellum shape of Geoblasta pennicillata, a sexually deceptive orchid - Benitez-Vieyra, Santiago Miguel (2009)
By mimicking shape and female mating pheromones, flowers of sexually deceptive orchids attract sexually excited males which pollinate them while trying to copulate. Although many studies have demonstrated the crucial importance of odour signals in these systems, most flowers pollinated by pseudocopulation resemble, at least superficially, an insect body and these visual cues may be important to cheat pollinators. In this 2-year study, we show that the shape of the labellum of Geoblasta pennicillata is a target of pollinator-mediated natural selection. Contrary to our expectations, plants with a labellum shape more similar to female wasps were not favoured. The strength and pattern of phenotypic selection varied between study years and sexual functions. Although selection through female success was probably associated to the fine-tuning of the mechanical fit between flower form and male wasp, shape was the target of natural selection through male success in both study years indicating that male wasps use this trait when choosing flowers. The imperfect mimicry and patterns of selection observed indicated that an exact imitation is not needed to attract and deceive the pollinators and they suggested a receiver perceptual bias towards uncommon phenotypes.